Мовна практика українців як вияв традиційної культури землеволодіння - Дидик-Меуш, Ганна (Slavia Orientalis, 2025)
The article considers the topoapellatives in Ukrainian documents of the 16th–17th centuries: the names of land boundaries and the names of special boundary marks. The conducted studies of the texts Study of Ukrainian monuments of the 16th–17th centuries indicate the use of predominantly native Proto-Slavic names forof landscape objects, withand only one name beingis a borrowing. The texts of Ukrainian documents reflect the ability of the language to use internal resources to nominate important processes related to land law. We are talking about the use of words of everyday speech in a new role, namely as terms of land law due to the expansion of the semantic structure of such words. Another important process of word usage is the hyper-hyponymic connections in the system of topoapellutives. These names reflect a rich and ancient culture of land ownership, and also the deep attachment of Ukrainians to their land, their past and future.